Perbandingan Alat X-Ray Dengan Olympus Element-S Untuk Menentukan Hasil Kadar Nikel Di Pt. Nikelindo Jaya Nusantara Siuna, Kabupaten Banggai, Provinsi Sulawesi Tengah - Atuna, Blair; Hendro Purnomo; Ag. Isjudarto (Retii, 2023)
Nikelindo Jaya Nusantara is a contractor company that carries out mining operations in the IUP area of PT. Prima Dharma Karsa, which is engaged in mining Laterite Nickel ore located in Siuna Village, Banggai Regency, Central Sulawesi Province. Nickel laterite is one of the mineral deposits resulting from the chemical weathering process of ultramafic rocks which results in residual and secondary enrichment of Ni, Fe elements. In lateritic nickel ore (ore) mining activities, changes in the elemental content of nickel ore often occur. While still in the mining front and after being transferred to the barge, it is possible that the changes in grades that occur experience quite significant differences. The purpose of this study is to determine the comparison between the two analytical tools to analyze the value of Nickel content in the Mining Front and on the Barge, then to find out how many changes in grades occur in lateritic nickel minerals from the mining front after being transferred to the Barge and find out the factors that cause changes. that rate. Grade data on nickel laterite minerals from the mining front using the Olympus tool is 2.11% and x-ray is 2.19% with a dilution of 3.79% and a difference in content of 0.08%. The Fe content from the mining front using Olympus is 31.50% and using X-Ray is 30.70% so that the dilution content is 2.54%. Furthermore, the minerals from the Barge using the Olympus tool are 1.99% and Xray are 2.04% with a dilution content of 2.51%. The Fe content from the Barge using Olympus was 26.85% and using X-Ray was 28.48% so that the dilution content was 6.07%. Changes in these levels occur due to factors due to accuracy problems in sampling, sample preparation that ignores procedures, and also human errors such as errors in sampling code, changing samples when delivered to preparation. So if you refer to these data, the tool must recalibrate even though the difference in dilution levels produced is quite low, but it is better if it is recalibrated in a shorter period of time, so that the difference in dilution levels is not too great, which causes less the accuracy of the grades displayed from the two tools even though they still meet the specifications for the grade of nickel minerals according to the company's target.